The Infrared-bright SW Knots in the Complex Ejecta of VY CMa - Roberta M. Humphreys; Terry J. Jones; Kris Davidson; A. M. S. Richards; R. Ravi; A. P. Singh; L. M. Ziurys (The Astronomical Journal)
The red hypergiant VY CMa is remarkable for its very visible record of high-mass-loss events observed over the range of wavelengths from the optical and infrared to the submillimeter region with Atacama Large Millimeter/submillimeter Array (ALMA). The SW Clump or SW knots are unique in the ejecta of VY CMa. Except for the central star, they are the brightest sources of dusty infrared emission in its complex ejecta. In this paper we combine the proper motions from the Hubble Space Telescope images, and infrared fluxes from 2 to 12 μ m with the ^12 CO images from ALMA to determine their ages and mass estimates. The SW knots were ejected more than 200 yr ago with an active period lasting about 30 yr, and with a total mass in the Clump > 2 × 10 ^−2 M _⊙ .